2017
DOI: 10.22336/rjo.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Eales’ disease a case report

Abstract: Introduction. Eales disease is an idiopathic peripheral vascular occlusive disease characterized by inflammation, ischemia, and retinal neovascularization and is hallmarked by recurrent vitreous hemorrhages and vision loss. Case report. We present a case of a 48-year-old female with recurrent floaters and decreased vision in her right eye. The onset of symptoms was in 2007 when a diagnose of retinal vasculitis was made. She had no accompanying systemic signs and symptoms and no history of ocular trauma or prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Zhao et al reported that 83% of the patients included in their analysis presented a positive Mantoux test [7]. In our study, we obtained similar results; our patient presented positive Mantoux and QuantiFERON TB Gold tests Immunity-related mechanisms have also been included in various studies, revealing an association between HLA B5, DR1, DR4, autoimmune disease, and Eales disease etiologies [6,12,14].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Zhao et al reported that 83% of the patients included in their analysis presented a positive Mantoux test [7]. In our study, we obtained similar results; our patient presented positive Mantoux and QuantiFERON TB Gold tests Immunity-related mechanisms have also been included in various studies, revealing an association between HLA B5, DR1, DR4, autoimmune disease, and Eales disease etiologies [6,12,14].…”
Section: Discussionsupporting
confidence: 86%
“…Immunity-related mechanisms have also been included in various studies, revealing an association between HLA B5, DR1, DR4, autoimmune disease, and Eales disease etiologies [ 6 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eales’ disease is an idiopathic peripheral retinal vasculopathy characterized by vasculitis, ischemia, retinal neovascularization, and recurrent vitreous hemorrhages [ 1 ]. Eales’ disease is a diagnosis of exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it affects males more than females at 20-40 years of age [3]. Although a unilateral complaint is more frequent, 50%-90% of the patients have bilateral involvement [2,4]. The most prevalent etiological theory is hypersensitivity to tuberculinprotein that develops after exposure to Mycobacterium tuberculosis [5].…”
Section: Introductionmentioning
confidence: 99%